The Role of the Notary in Making the Deed of Establishment of Savings and Loans Cooperative - Dimas, M. (TABELLIUS: Journal of Law, 2023)
Cooperative legal entities in practice cannot be denied that these legal entities have cases that can harm the Cooperative in question, where the problem lies in the result of committing a form of negligence and even intentional perpetration by the founders of the Cooperative. On a scientific basis, writing is motivated to carry out a scientific study in the form of systematic and fundamental research with the title "The Role of Notaries in Making Deeds of Establishment of Savings and Loans Cooperatives (Case Study in Pekalongan Regency)". The research method that used in this study is the empirical juridical approach, which is a study that besides looking at the positive legal aspects also looks at its application or practice in the field in the form of interviews or photographs, interest and costs as a result of mistakes or negligence in making cooperative decisions. Keywords: Cooperative; Deed; Loans; Savings.